Shared Genetics of Multiple System Atrophy and Inflammatory Bowel Disease. Issue 2 (27th October 2020) - Shadrin, Alexey A.; Mucha, Sören; Ellinghaus, David; Makarious, Mary B.; Blauwendraat, Cornelis; Sreelatha, Ashwin A.K.; Heras‐Garvin, Antonio; Ding, Jinhui; Hammer, Monia; Foubert‐Samier, Alexandra; Meissner, Wassilios G.; Rascol, Olivier; et al.
Abstract: Background: Multiple system atrophy (MSA) is a rare neurodegenerative disease characterized by intracellular accumulations of α‐synuclein and nerve cell loss in striatonigral and olivopontocerebellar structures. Epidemiological and clinical studies have reported potential involvement of autoimmune mechanisms in MSA pathogenesis. However, genetic etiology of this interaction remains unknown. We aimed to investigate genetic overlap between MSA and 7 autoimmune diseases and to identify shared genetic loci. Methods: Genome‐wide association study summary statistics of MSA and 7 autoimmune diseases were combined in cross‐trait conjunctional false discovery rate analysis to explore overlapping genetic background. Expression of selected candidate genes was compared in transgenic MSA mice and wild‐type mice. Genetic variability of candidate genes was further investigated using independent whole‐exome genotyping data from large cohorts of MSA and autoimmune disease patients and healthy controls. Results: We observed substantial polygenic overlap between MSA and inflammatory bowel disease and identified 3 shared genetic loci with leading variants upstream of the DENND1B and RSP04 genes, and in intron of the C7 gene. Further, the C7 gene showed significantly dysregulated expression in the degenerating midbrain of transgenic MSA mice compared with wild‐type mice and had elevated burden of protein‐coding variants in independent MSA and inflammatory bowel disease cohorts. Conclusion: Our study provides evidence of shared genetic etiology between MSA and inflammatory bowel disease with an important role of the C7 gene in both phenotypes, with the implication of immune and gut dysfunction in MSA pathophysiology. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.